Factors Influencing Creative Employees: An Integration of Transformational Leadership Theory in The Case of Start-ups Employees in Indonesia - Dea Farahdiba; Nasmah Maleta Sekar Mahirah; Putri Angelique Nabila Maengkom (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: In today's competitive business environment, a start-up must attract and retain employees with a high level of creativity. The effects of intrinsic motivation, dimensions of transformational leadership, and personal factors on employee creativity are investigated”the physical space of the workplace as a moderator between the transformative leadership and inventiveness dimensions. Design/Methods/Approach: This study employs a quantitative strategy using the Partial Least Squares (PLS) method for data analysis with the assistance of SmartPLS. Based on the findings, we know that 101 employees of Indonesian start-ups with a shorter history of employment than a year participated in this study. Findings: Inspiring motivation, idealized influence, intellectual stimulation, and personal consideration were all found to increase employees' inventiveness. However, results did not improve when the physical work environment was moderated between the four dependent variables: inspirational motivation, idealized influence, intellectual stimulation, and individual consideration of employees' creativity. Originality: A leader's idealized influence and intellectual stimulation on their employees is the dimension of transformational leadership used in this study. Practical/Policy implication: This study's significance is that it contributes new knowledge to the literature on the factors that affect employee creativity in Indonesia. Moreover, they can provide valuable input for company management to boost employee creativity by inspiring further development.